Introduction to lipidomics from bacteria to man - Leray, Claude (CRC Press, 2013)
"The first comprehensive book on lipidomics, this long-awaited work inventories the huge variety of lipid molecules present in all aspects of life. It uses sensitive analytical techniques, such as mass spectrometry, to characterize structures and simplify the association of names with their appropriate structures. Fulfilling the spirit of inclusiveness, it details structures from marine ecosystems, little known structures from bibliographic data, cultural references and context, biological functions, and possible pharmacological properties. The text is highly informative and educational while simultaneously being anecdotal and interesting to read"--